Examining food addiction associations with socioeconomic status and prevalence among food pantry users, and lack of SNAP access in Nebraska due to prior drug convictions - Grossman, Anna (Tufts University Tisch Library, 2026)
Thesis (Ph.D.)--Tufts University, 2026.; Submitted to the Dept. of Food and Nutrition Policy and Programs.; Advisor: Aviva Must.; Committee: Kimberly Dong, and Wenhui Feng.; Keywords: Nutrition, Public health, and Public policy